MACRONUTRIENT K VARIATION IN MUNG BEAN SPROUTS WITH LUNAR PHASES - Deep, Kanan; Mittal, Raj (European Scientific Journal, ESJ, 2014)
The cosmos in atmosphere exerts variable force depending upon the relative positions of moon, sun and earth (lunar phase) and affects the plants/crops. Here, a lunar activity on sprouting of mung beans in terms of their potassium contents and sprout lengths has been tested. Under the similar mung processing in different moon phases, a rhythmic character of sprout lengths and potassium contents was observed. The statistical analysis of observations rules out the effect of moon phases on sprout lengths and predicts just randomness of the length variations. While the potassium content variations are prominent; Near New Moon, First Quarter and after Full Moon (Super Moon) phases there is rise in the contents. All this has been explained in terms of Earth’s magnetic field variations with moon phases, thereby affecting the contents of minerals in sprouts.